Levantamento de nematoides entomopatogênicos em áreas agrícolas e influência da temperatura e do substrato na sobrevivência, multiplicação e armazenamento - Brida, Andressa Lima de [UNESP] (2015)
Entomopathogenic nematodes (EPNs) show promising for biological control of pests. The abiotic factors, temperature, soil types and substrates, may influence the survival of infective juveniles storage and field conditions. The objectives of this study were to isolate and identify species of EPNs collected in areas of forestry, annual and fruit crops in Brazil; assess the period of mortality of larvae Galleria mellonella after infection of Heterorhabditis amazonensis IBCB 24, the emergency period and IJs (infective juveniles) multiplied during the 30-day period in five temperatures; evaluate the influence of temperature on survival IJs of Steinernema carpocapsae IBCB 02 Heterorhabditis amazonensis IBCB 24 and Steinernema feltiae IBCB 47 storage conditions; evaluate the influence of light and substrate on juvenile infection capacity of isolates IBCB 06 Steinernema brazilense, IBCB 02 Steinernema carpocapsae, IBCB 47 Steinernema feltiae and IBCB 24 Heterorhabditis amazonensis in larvae G. mellonella and evaluate the use of different substrates to prolong the survival of IJs of S. brazilense IBCB 06 and H. amazonensis IBCB 24 storage conditions. This study was divided into five chapters. After collecting data, the species were identified as H. amazonensis, S. rarum, M. rainai and O. tipulae. The at temperatures of 26°C and 30°C gave the shortest time period (three days) for the crawler mortality caused by H. amazonensis in G. mellonella. The shortest duration for emergency IJs was found at 30°C temperature (9.4 days). The average number of IJs produced at 26°C (229.563) was higher at all temperatures studied, but no statistical difference when compared to 30°C IJs produced in the temperature (127.157). The temperature of 22°C (223.886) did not differ statistically from the lower temperature ...